2022
DOI: 10.1155/2022/3512621
|View full text |Cite
|
Sign up to set email alerts
|

The Research of Sequence Shadowing Property and Regularly Recurrent Point on the Double Inverse Limit Space

Abstract: According to the definition of sequence shadowing property and regularly recurrent point in the inverse limit space, we introduce the concept of sequence shadowing property and regularly recurrent point in the double inverse limit space and study their dynamical properties. The following results are obtained: (1) Regularly recurrent point sets of the double shift map σ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…At present, shadowing property has gradually become an important theory and concept in dynamical system. Relevant results are seen in [1][2][3][4][5][6][7][8][9][10][11]. For example, Wang and Zeng [1] proved that if f has q-average tracking property, then f is chain transitivity under some conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, shadowing property has gradually become an important theory and concept in dynamical system. Relevant results are seen in [1][2][3][4][5][6][7][8][9][10][11]. For example, Wang and Zeng [1] proved that if f has q-average tracking property, then f is chain transitivity under some conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wu [2] showed that f has tracking property and σ has tracking property are equivalent. Ji et al [3] proved that f ∘ g has the Lipschitz shadowing property and σ f ∘g has the Lipschitz shadowing property are equivalent in the double inverse limit space. Ahmadi and Hosseini [4] gave that δ-ergodic pseudo-orbit of a system means chain mixing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation